PENGARUH LATIHAN AEROBIK TERHADAP KUALITAS HIDUP PASIEN PENYAKIT PARU OBSTRUKTIF KRONIK - Anita Gandaria Purba; Dian Anggriyanti; Nur Hamida Pohan (JURNAL PENGMAS KESTRA (JPK), 2021)
Patients with COPD experience a fundamental inability to breathe in the form of shortness of breath, chronic cough, chronic sputum production, and limited activity. Aerobic exercise for COPD sufferers aims to reduce symptoms, improve quality of life and increase daily activities. This study aims to determine the effect of aerobic exercise on the quality of life of COPD patients. This research is a quantitative study using a quasi-experimental design with a pretest-posttest research design, using the sampling technique is purposive sampling with 44 respondents. Retrieval of data using a quality of life questionnaire for COPD patients. The results of the paired t test showed a value of p <0.000, which means that p <0.05, this shows in general that aerobic exercise has an effect on the quality of life of COPD patients. COPD sufferers who routinely do aerobic exercise regularly will increase their perfusion so that tissue needs can be fulfilled and COPD symptoms, especially shortness of breath, will decrease.